Interactions between Simulant Vitrified Nuclear Wastes and high pH solutions: A Natural Analogue Approach. (20th January 2017) - Mann, Colleen; Thorpe, Clare; Milodowski, Antoni E.; Field, Lorraine P.; Shaw, Richard P.; Boast, Luke; Hand, Russell; Hyatt, Neil C.; Provis, John L.; Corkhill, Claire L.
ABSTRACT: This study details the characterization of a glass sample exposed to hyperalkaline water and calcium-rich sediment for an extended time period (estimated as 2 - 70 years) at a lime (CaO) waste site in the UK. We introduce this site, known as Peak Dale, in reference to its use as a natural analogue for nuclear waste glass dissolution in the high pH environment of a cementitious engineered barrier of a geological disposal facility. In particular, a preliminary assessment of alteration layer chemistry and morphology is described and the initiation of a long-term durability assessment is outlined.